Tax excess policies in Colombia (2018)
In this document the tax exemptions in colombia are analyzed, with respect to the income tax and value-added IVA, and its influenceon the Gini index, the economic and social developent of the state and assuming if colombia is in good economic growth.inequality in relation to the tax system, them we observe the changes in the tax system in the laws and we discriminate the IVA and income taxes.Finally, we study the exemptionsof each one and the possible applicability of the best practices.